(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1867)
This article discusses the buildings and artefacts found at the settlement of Skara Brae, as excavated by Mr William Watt. The author provides the dimensions of the ruined buildings, as well as the details and locations of any items found during the excavation. He also suggests the methods by which some of the artefacts might have been created by the original inhabitants. A list of items found at Skara Brae and illustrations of the site are included.